PENGARUH PELAKSANAAN PRINSIP-PRINSIP GOOD GOVERNANCE TERHADAP KINERJA PEMERINTAH DESA - Hengki Ariawan; Subur Bahri; Sri Wilujeng (Fakultas Ilmu Sosial dan Ilmu Politik Universitas 17 Agustus 1945 Banyuwangi, 2021)
Abstract: Effect Of The Implementation Of The Principles Of Good Governance On The Performance Of The Village Government (Case Study In Wonosobo Village, Srono District, Banyuwangi Regency). In the current era of globalization, the Indonesian state in terms of governance is experiencing an advancement in the times. Therefore, the government is demanded for reforms in the government system, both those in the center and those in the regions, including in the village government. But in the office of the village head Wonosobo still not fully apply the principles of good governance, such as lack of responsibility with the work provided and lack of transparency in the administration of government. The research method is quantitative. The types of data used are questionnaires, interviews and documentation. Data analysis used product moment correlation statistics which resulted in the influence of the implementation of the principles of good governance on the performance of the village government. The benefit of this research is to provide information and input to the wonosobo village government regarding the implementation of the principles of good governance on the performance of the village government so that they can provide more optimal results of service.